(untitled) (Linguostylistic Studies, 2015)
The concept of comic was clarified in the article, particularly the theory of comic and the different types of comic (humor, satire and irony), verbal and situational verbal comic. The connection comic with the specifics of national character was noted, it is especially true of comic verbal. For stylistic analysis of comic texts is important to separate them into two types: actual comic texts and texts with elements of comic. This classification takes into account, first of all, the place of comic in the structure of the analyzed texts. Accordingly, the two algorithms of stylistic analysis of these two types of comic texts were presented. Also some examples of typical and most frequent verbal and situational verbal means of comic expression in the anecdote as an elementary genre of comic were shown (comic persona, comic situation, pun, antiphrasis transformed idiom and its types). Key words: comic, comic text, stylistic analysis. References